Human Capital Investment Development Strategy in Indonesia - Veramika br Sembiring (Kusuma Negara Business School, 2021)
In its implementation, increasing human resources can also be done through educational partnerships to improve formal education, which is still so low. For this reason, all parties, both private and bureaucrats, jointly manage human resources as